2002
DOI: 10.1179/016164102101199701
|View full text |Cite
|
Sign up to set email alerts
|

Vascular tunnel construction in the treatment of severe brain swelling caused by trauma and SAH. (Evidence based on intra-operative blood flow measure)

Abstract: Decompressive craniectomy with durotomy, is possible as a last resort therapy for severe traumatic brain swelling. Although the method successfully diminishes the ICP, partial or total vascular insufficiency occurs in the herniated part of the brain. The actual cause of the insufficiency is most likely due to the compression of the cortical veins and arteries supplying the herniated brain, caused by shearing and pressure forces between the dural edge and brain tissue. Furthermore venous congestion may induce e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Table 6 gives the odd ratios of having a poor outcome (GOS < 4) or of dying (GOS 1) for the different determinants. In the secondary DC group, none of the early characteristics of head trauma (pupil dilatation, severity of trauma, mechanism of Primary DC= from the onset of management; early DC= within 24 hours= secondary DC= after 24 hours; uDC= unilateral DC; bDC= bilateral DC; MMM= maximum medical management; PVS= persistent vegetative state 41 22 patients all secondary DC 41% good recovery, 18% severe disability, 23% PVS and 18% died Taylor 2001 12 27 patients secondary bDC ICP is lower post bDC ; reduced risk of death; reduced risk of PVS with bDC compared to MMM Coplin 2001 42 29 patients, primary DC (12) vs craniotomy (17) DC reduced mortality while yielding equivalent neurologic outcome for survivors Csokay 2002 43 28 patients all secondary DC Reduced mortality from 80-90% with MMM to 40% with DC Kontopoulos 2002 44 9 patients, DC day 1 to11 Mortality rate 22%, severe disability 11%, good recovery 66% Albanèse 2003 8 40 patients, primary < 24 h (27) secondary > 24h (13) Early DC: 20% good recovery, 30% PVS, 50% died Secondary DC: 38% good recovery, 38% PVS, 20% died Meier 2003 45 80 patients Primary (53) vs secondary (27) Pooled outcome analysis 47 19 patients 68% good outcome, 16% poor outcome, 11% mortality Chibbaro 2007 10 48 patients, early < 18 h (28) secondary > 18h (20) Determinants of good outcome: early DC, younger age, higher preDC GCS; 56% good GOS with early DC Jagannathan 2007 48 23 patients 30% mortality. Of survivors, 83% good outcome at 2 years, Olivecrona 2007 21 patients 71% favorable outcome (vs 61% in non-DC controls), mortality 14% in both groups Howard 2008 24 40 patients Primary (16) vs secondary (24) Pooled analysis.…”
Section: Predictors Of Outcomementioning
confidence: 99%
“…Table 6 gives the odd ratios of having a poor outcome (GOS < 4) or of dying (GOS 1) for the different determinants. In the secondary DC group, none of the early characteristics of head trauma (pupil dilatation, severity of trauma, mechanism of Primary DC= from the onset of management; early DC= within 24 hours= secondary DC= after 24 hours; uDC= unilateral DC; bDC= bilateral DC; MMM= maximum medical management; PVS= persistent vegetative state 41 22 patients all secondary DC 41% good recovery, 18% severe disability, 23% PVS and 18% died Taylor 2001 12 27 patients secondary bDC ICP is lower post bDC ; reduced risk of death; reduced risk of PVS with bDC compared to MMM Coplin 2001 42 29 patients, primary DC (12) vs craniotomy (17) DC reduced mortality while yielding equivalent neurologic outcome for survivors Csokay 2002 43 28 patients all secondary DC Reduced mortality from 80-90% with MMM to 40% with DC Kontopoulos 2002 44 9 patients, DC day 1 to11 Mortality rate 22%, severe disability 11%, good recovery 66% Albanèse 2003 8 40 patients, primary < 24 h (27) secondary > 24h (13) Early DC: 20% good recovery, 30% PVS, 50% died Secondary DC: 38% good recovery, 38% PVS, 20% died Meier 2003 45 80 patients Primary (53) vs secondary (27) Pooled outcome analysis 47 19 patients 68% good outcome, 16% poor outcome, 11% mortality Chibbaro 2007 10 48 patients, early < 18 h (28) secondary > 18h (20) Determinants of good outcome: early DC, younger age, higher preDC GCS; 56% good GOS with early DC Jagannathan 2007 48 23 patients 30% mortality. Of survivors, 83% good outcome at 2 years, Olivecrona 2007 21 patients 71% favorable outcome (vs 61% in non-DC controls), mortality 14% in both groups Howard 2008 24 40 patients Primary (16) vs secondary (24) Pooled analysis.…”
Section: Predictors Of Outcomementioning
confidence: 99%
“…Efforts have been made to alleviate some of these problems by resorting to various alternative, novel surgical techniques, [13][14][15] and modifications 16,17 with varied amount of success; however, neither have they gained universal acceptance nor have they been able to take care of all the drawbacks. A wide durotomy and expansive duraplasty have been advocated to accommodate the surplus brain volume caused by the postoperative edema 18 in view of the perceived inevitability of the postcraniectomy cerebral edema.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, significant reductions in brain edema and vascular insufficiency were reported, together with a 40% improvement in mortality. 66 We believe that hemicraniectomy does improve survival. However, our experience failed to demonstrate a significant difference in functional outcome in patients matched with comparable initial GCS and trauma score.…”
Section: Decompressive Craniectomymentioning
confidence: 93%